Pengaruh Interval Penyiraman dan Dosis Pupuk terhadap Persentase Hidup Semai Acacia crassicarpa: Effect of Watering Interval and Fertilizer Dosage on the Survival Rate of Acacia crassicarpa Seedlings - Sulviana (Universitas Muhammadiyah Palu, 2025)
Climate change increases the risk of drought and threatens the success of forest rehabilitation by reducing seedling survival. This study aimed to determine the effects of watering interval and fertilizer dosage on the survival rate of Acacia crassicarpa seedlings under greenhouse conditions. The research was conducted at the Permanent Nursery, Faculty of Forestry, Tadulako University, using a completely randomized design arranged in a split-plot pattern. The main plot factor was watering interval (2, 4, and 6 days), and the subplot factor was NPK fertilizer dosage (0, 1.5, 3, and 4.5 g per seedling), with three replications and six seedlings per replicate (a total of 216 seedlings). Analysis of variance showed that watering interval (F = 6.30; p < 0.05) and fertilizer dosage (F = 50.65; p < 0.01) significantly affected seedling survival, whereas their interaction was not significant (F = 1.35; p > 0.05). The highest survival rate was obtained under a 4-day watering interval (81%) and a low fertilizer dosage of 1.5 g (94%), while higher fertilizer dosages (3 and 4.5 g) reduced survival to 55% and 33%, respectively. These findings indicate that A. crassicarpa seedling viability is sensitive to high fertilizer concentrations but performs optimally under moderate watering frequency, providing useful implications for silvicultural management in drought-prone tropical regions.